Strength of a Tower for a High-Rise Hybrid Timber Building: A study of how different parameters affect the dynamic performance of a building - Kallmér, Isak; Alkhateb, Mahmoud (My University, 2024)
One of the most common construction materials for tall buildings is concrete. Alternatives to concrete buildings are timber and hybrid buildings. Two main advantages of building in timber are that it is environmentally friendly and the strength-toweight ratio is large. The main challenge is also tied to timber’s lightweight nature, which significantly contributes to wind-induced accelerations. These accelerations have adverse effects on the occupants, leading to a threshold beyond which they become unacceptable. Another challenge arises from timber’s inherent weakness compared to concrete, which implies that there may be a limit to the height a building can reach while maintaining reasonable dimensions. The thesis investigates how different parameters affect the dynamic response of a tall building but also in relation to load-bearing capacity. The project was performed for a fictitious building with different structural systems. Both FE analyses and hand calculations were performed to verify the serviceability limit state criteria with a major focus on accelerations together with verifying the load-bearing capacity of the structural timber elements in a building. The investigations showed that the dynamic performance of the building increased when the amount of concrete increased. The increase also resulted in an increased utilization ratio in the ultimate limit state. Based on the results, it was concluded that in most cases, it was the acceleration criterion that was the most critical in the design of a timber hybrid building. The main parameters determining the dynamic performance are the stiffness of the building and the equivalent mass. An increase in mass and possibly also the stiffness of the building will decrease the acceleration of the building. For example, thicker wall elements will contribute to larger mass and stiffness. The structural system with walls and slabs performed dynamically better than a beam and column system with less mass and stiffness, which becomes more prone to wind-induced vibrations.
Keywords: Hybrid building, Tall Hybrid Timber Building, CLT, Glulam, Structural Dynamcis, Wind Dynamcis, Finite Element Analysis, Acceleration, ULS, SLS